The Effect of Product Quality and Promotion on Purchasing Decisions: Study at A Company Engaged in The Field of Weapons Systems and Commercial Products - Dian Sutisna; Soelaeman Sukmalana; Rd Okky Satria; Rd Rahadian Arby (Jurnal Ekonomi, Bisnis & Entrepreneurship, 2023)
As a nation endowed with a diverse cultural heritage and vast reserves of natural resources, Indonesia requires the acquisition and utilization of state-of-the-art defense equipment and technology. The Panzer Anoa is a military armored vehicle manufactured by a company specializing in the production of armament systems and commercial products. This vehicle serves the purpose of personnel transportation, commonly referred to as armored personnel carriers (APCs). Over the past three years, there has been a noticeable decrease in the sales of the Panzer Anoa, a product manufactured by a company producing Main Equipment Armament Systems and commercial goods. According to the data provided by the company operating in the Main Armament System Equipment industry and commercial products, 25 units were sold within three years. This figure falls significantly short of the predetermined target of 72 units, resulting in a sales percentage of merely 34.72%. The study employed a quantitative research methodology characterized by a descriptive and verification approach. The sample consisted of 54 respondents selected using a stratified random sampling technique. In gathering supporting data and information, primary data is utilized, specifically in the form of questionnaire data directly obtained from a company operating in Armament Systems Primary Equipment and commercial products. The study's findings demonstrated that each statement item exhibited validity, as indicated by values exceeding 0.30 and reliability, with results surpassing 0.60. The study findings indicate that the product quality factor exhibited a high significance level, with a coefficient of 0.981. Similarly, the promotion factor strongly influenced the purchase decision, as evidenced by its coefficient of 0.977. Furthermore, the purchase decision itself was found to be significantly influenced by various factors, with a coefficient of the t-test yielded T count values of 3.981 (p < 0.001) and 2.826 (p < 0.001), both of which exceed the critical T table value of 2.007. attributable to other factors. Another factor that has yet to be examined is the value of 0.263, or 26.3%. Furthermore, it is noteworthy that the influence of product quality is more pronounced, with a total effect of 0.4361 or 43.61%, compared to the total effect of promotion, which stands at 0.3002 or 30.02%. It is advisable for companies operating in the Armament System Primary Equipment and commercial products sector to place a high emphasis on product quality. These results can be achieved by consistently enhancing the features of the Anoa Panzer and streamlining its operational processes.